Final data of an Italian multicentric survey about counseling for smoking cessation in patients with diagnosis of a respiratory disease. (10th May 2017) - Capelletto, Enrica; Rapetti, Simonetta Grazia; Demichelis, Sara; Galetta, Domenico; Catino, Annamaria; Ricci, Donata; Moretti, Anna Maria; Bria, Emilio; Pilotto, Sara; Bruno, Arianna; Valmadre, Giuseppe; Bandelli, Gian Piero; et al.
Abstract: Introduction: Smoking is the major risk factor for cancer and several respiratory diseases. Quitting smoking at any point of life may increase the effectiveness of treatments and improve prognosis of patients with any pulmonary disease, including lung cancer. However, few institutions in Europe offer to patients adequate counseling for smoking cessation. Objectives: Aim of this study was to investigate the level of counseling for smoking cessation offered by healthcare professionals to patients and their appreciation towards the intervention itself. Methods: Between January 2013 and February 2016, 490 patients, diagnosed with a respiratory diseases, were prospectively evaluated with an anonymous survey developed by WALCE (Women Against Lung Cancer in Europe). Results: The majority of patients enrolled (76%) declared to have stopped smoking after the diagnosis of a respiratory disease, 17% to smoke less, 7% to continue smoking. Patients who reported to have never received any counseling for smoking cessation were 38%. Almost 73% of the other patients reported a positive judgment about the quality of healthcare's intervention. Despite these favorable considerations, 83% of patients have disclosed they simply quit smoking overnight without help, 5% have used electronic cigarettes, 5% nicotine replacement treatments, 4% dedicated books, 3% have attended a referral clinic. Conclusions: Considering all the smoking‐related side effects, greater efforts should be made in order to better support patients in smoking cessation. Smoking should be considered as a real physical disorder and similar surveys should be encouraged with the aim to fight the 'stigma' of smoking that still exists among patients.